Disease and Empire: Women and Caregiving in Colonial Jamaica, 1850-1920 - Green-Stewart, Sandria L. (My University, 2022)
This research about women’s caregiving experiences in Jamaica uses the conceptual frameworks of intersectionality and anti-racist feminist perspectives to interpret and analyze the experiences of informal and formally trained nurses and folk healers in post-slavery Jamaica. This study explores how race, colour, class, gender, citizenship, and national identity intersected to define and shape women’s experiences as caregivers in Jamaica between the 1850s and the 1910s. By integrating scholarly interpretations about a plural health system with case studies about the management of diseases and developments in nursing, this research presents an inclusive analysis of female caregivers (British, Euro-American, and Afro-Jamaican nurses and folk healers) in post-slavery Jamaica. The late nineteenth to the early twentieth centuries was the period of the “new” imperialism characterized by the growth of caregiving and medical philanthropy in aiding the expansion of imperial pursuits and the civilizing mission of empires (British and US). Caregiving reveals how gender, race, class, and national identity intersected to shape the management of diseases in post-slavery Jamaica. On the one hand, formal caregiving was a tool for empire-building through colonial medical policies that aimed to heal the bodies and “civilize” the mentality of colonized peoples. On the other hand, informal caregiving empowered oppressed people to reshape cultural customs by adapting healing and religious practices to challenge British imperialism and claim citizenship.
Keywords: Medical History; Nursing History; 19th century epidemics; Folk healers